Cover Feature: Reactivity of the Bicyclic Amido‐Substituted Silicon(I) Ring Compound Si4{N(SiMe3)Mes}4 with FLP‐Type Character (Chem. Eur. J. 69/2021). Issue 69 (18th November 2021) - Schwedtmann, Kevin; Quest, Michael; Guddorf, Benedikt J.; Keuter, Jan; Hepp, Alexander; Feldt, Milica; Droste, Jörn; Hansen, Michael Ryan; Lips, Felicitas
Abstract : The unsaturated bicyclo[1.1.0]tetrasilatetraamide Si4 {N(Mes)SiMe3 }4 shown in the upper right corner has two threefold‐coordinated silicon atoms that show zwitterionic character. This gives the molecule intramolecular FLP‐type character. Different acids such as AlBr3, BH3, H + and the base NHCMe4 can simply coordinate to the threefold‐coordinated silicon atoms. These reagents "click" in place just like magnetic sticks and steel balls from a molecular construction kit do. More information can be found in the Full Paper by F. Lips et al. (DOI: 10.1002/chem.202103101 ).